Risk of Autoimmune Diseases in Patients With Interstitial Cystitis/Bladder Pain Syndrome: A Nationwide Population-Based Study in Taiwan - Yueh, Hann-Ziong; Yang, Min-Hsin; Huang, Jing-Yang; Wei, James Cheng-Chung (Frontiers in Medicine, 2021)
Objective: The association between autoimmune diseases (ADs) and interstitial cystitis/bladder pain syndrome (IC/BPS) has long been investigated. However, the lack of comprehensive descriptions of patients in the literature has made comparison and evaluation impossible. We aim to investigate the risk of systemic ADs in patients with IC/BPS in Taiwan using a population-based administrative database. Methods: This study evaluated 1,095 patients newly diagnosed with IC/BPS between 2000 and 2013, using data from Taiwan's National Health Insurance Research Database. These patients were randomly matched by demographic characteristics with a comparison cohort of individuals without IC/BPS at a ratio of 1:20. Cox proportional hazards regression analysis was used to analyze the risk of ADs, adjusting for age, sex, urbanization, length of hospital stay, and comorbidities adjustment. Sensitivity analysis by propensity score was used to adjust for confounding factors. Results: The adjusted Hazard Ratio (aHR) of ADs for IC/BPS patients was 1.409 (95% CI 1.152–1.725). The subgroup analysis indicated that female or 45–60 years of age had a greater risk of ADs. Furthermore, the subgroup analysis of primary outcomes indicated that IC/BPS had greater incidence with Hashimoto's thyroiditis (aHR = 2.767, 95% CI 1.039–7.368), ankylosing spondylitis (aHR = 2.429, 95% CI 1.264–4.67), rheumatoid arthritis (aHR = 1.516, 95% CI 1.001–2.296), and Sjogren's syndrome (aHR = 1.962, 95% CI 1.37–2.809). Conclusion: IC/BPS was associated with the development of ADs in our study population, especially Hashimoto's thyroiditis, ankylosing spondylitis, rheumatoid arthritis, and Sjogren's syndrome. Clinicians are recommended to be alert to the increased likelihood of developing ADs, particularly for middle-aged women.